2023
DOI: 10.1055/a-2133-8614
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis Delta Infection: A Clinical Review

Abstract: First discovered over 40 years ago, the hepatitis delta virus (HDV) is a unique RNA virus, requiring hepatitis B virus (HBV) antigens for its assembly, replication, and transmission. HBV and HDV can be acquired at the same time (coinfection) or HDV infection can occur in persons with chronic HBV (superinfection). Screening guidelines for HDV are inconsistent. While some guidelines recommend universal screening for all people with HBV, others recommend risk-based screening. Estimates of the global HDV prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…We did not detect the HBsAg-specific T cell and HBsAg-specific B cell responses due to the retrospective nature and the lack of blood samples of these patients. Last, coinfection of hepatitis D virus (HDV) in patients with CHB is associated with more severe hepatitis and an increased risk of disease progression [ 36 , 37 ]. However, screening for HDV is rarely performed in reality [ 37–39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not detect the HBsAg-specific T cell and HBsAg-specific B cell responses due to the retrospective nature and the lack of blood samples of these patients. Last, coinfection of hepatitis D virus (HDV) in patients with CHB is associated with more severe hepatitis and an increased risk of disease progression [ 36 , 37 ]. However, screening for HDV is rarely performed in reality [ 37–39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A breakthrough for the treatment of HDV was the approval of bulevirtide (BLV) (also known at Myrcludex B or hepcludex) [30] in some countries. BLV is derived from the myristoylated preS1 sequence (amino acids 1–48) and targets NTCP and blocks its interaction with HBV or HDV.…”
Section: Antiviral Therapies and Preclinical Models For Drug Evaluationmentioning
confidence: 99%
“…an estimated prevalence range of 4.5% to 14.6% in HBV-infected patients. 4 Several studies have demonstrated a significantly increased risk of HCC in patients with chronic HDV infection compared to those with HBV mono-infection. [3][4][5] However, co-infection with HDV was not mentioned and excluded, which might impact the results.…”
Section: Hdv Infection Affects Up To 72 Million Individuals Worldwide...mentioning
confidence: 99%